A REVIEW OF RHYNCHOSAUROIDES TIROLICUS ABEL, 1926 ICHNOSPECIES (MIDDLE TRIASSIC: ANISIAN-LADINIAN) AND SOME INFERENCES ON RHYNCHOSAUROIDES TRACKMAKER (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2002)
Rynhcosauroides tirolicus (Abel, 1926) is the first ichnite of Triassic tetrapods known from the South-eastern Alps. The recent discovery of new tracks and trackways also permits, for the first time, the documentation of trackway pattern and to calculate the dimensions and possible functional dynamics of the author of this form which appears peculiar to the upper Anisian deposits of the Southern Alps. A tentative palaeontological attribution of Rhynchosauroides tirolicus and other Middle Triassic Rhynchosauroides trackmaker suggest with some confidence, that the morphology of the trackmakers matches the structure of prolacertiform reptiles like Macrocnemus bassanii Nopcsa, 1931 if this latter is reconstructed with a not fully plantigrade manus and pes, but rather with a semi-plantigrade manus and a digitigrade pes.